Impact of On-the-Job Training on Nurses' Performance in Creating a Healing Environment and Clustered Nursing Care for Premature - Abdelaziz Hendy PhD; Sabah Saad Alsharkawy PhD; Zeinab Al-Kurdi PhD; Nahed Saied El-Nagger PhD; Ahmed Hendy PhD; Salwa Sayed MD; Khalid Al-Mugheed PhD; Samira Ahmed Alsenany PhD; Sally Mohammed Farghaly Abdelaliem PhD (SAGE Publishing, 2024)
Introduction Premature infants require specialized care, and nurses need to have specific skills and knowledge to provide this care effectively. Objective To evaluate the impact of an on-the-job training program on the improvement of nurses' knowledge and practice related to creation of a healing environment and clustering nursing procedures. Methods From January to April 2022, a study utilizing a one-group pre- and post-test design was conducted at NICUs in governmental hospitals. The study participants involved 80 nurses working in these NICUs. Researchers used predesigned questionnaire and checklist practice to collect the data pre and post the intervention. Results 37.5% of the participants were aged between 25 and less than 30 years, with a mean age of 28.99 ± 7.43 years. Additionally, 73.7% of the nurses were female, with a mean experience of 9.45 ± 3.87 years. Prior to the intervention, the study found that a majority of the nurses (62.4%) demonstrated poor knowledge. However, after the intervention, a significant improvement was observed, with 60.0% of the nurses demonstrated good knowledge. Likewise, prior to the intervention, the study revealed that the majority of the nurses (83.8%) exhibited incompetent practice. However, post-intervention, a substantial improvement was observed, with 81.3% of the nurses demonstrated competent practice. Conclusion On-the-job training had significant improvements in nurses' knowledge and practices regarding applying healing environments and clustering nursing care. On-the-job training is suggested as an adaptable, effective and low-cost technique to train nurses. To maintain the improvement achieved, ongoing instruction, feedback, assessment/reassessment, and monitoring are encouraged.